Three-Dimensional 123I-Meta-Iodobenzylguanidine Cardiac Innervation Maps to Assess Substrate and Successful Ablation Sites for Ventricular Tachycardia: Feasibility Study for a Novel Paradigm of Innervation Imaging. (June 2015) - Klein, Thomas; Abdulghani, Mohammed; Smith, Mark; Huang, Rui; Asoglu, Ramazan; Remo, Benjamin F.; Turgeman, Aharon; Mesubi, Olurotimi; Sidhu, Sunjeet; Synowski, Stephen; Saliaris, Anastasios; See, Vincent; et al.
Abstract : Background—: Innervation is a critical component of arrhythmogenesis and may present an important trigger/substrate modifier not used in current ventricular tachycardia (VT) ablation strategies. Methods and Results—: Fifteen patients referred for ischemic VT ablation underwent preprocedural cardiac 123 I- meta -iodobenzylguanidine ( 123 I- m IBG) imaging, which was used to create 3-dimensional (3D) innervation models and registered to high-density voltage maps. 3D 123 I- m IBG innervation maps demonstrated areas of complete denervation and 123 I- m IBG transition zone in all patients, which corresponded to 0% to 31% and 32% to 52% uptake. 123 I- m IBG denervated areas were ≈2.5-fold larger than bipolar voltage–defined scar (median, 24.6% [Q1–Q3, 18.3%–34.4%] versus 10.6% [Q1–Q3, 3.9%–16.4%]; P <0.001) and included the inferior wall in all patients, with no difference in the transition/border zone (11.4% [Q1–Q3, 9.5%–13.2%] versus 16.6% [Q1–Q3, 12.0%–18.8%]; P =0.07). Bipolar/unipolar voltages varied widely within areas of denervation (0.8 mV [Q1–Q3, 0.3–1.7 mV] and 4.0 mV [Q1–Q3, 2.9–5.6 mV]) and 123 I- m IBG transition zones (0.8 mV [Q1–Q3, 0.4–1.8 mV] and 4.6 mV [Q1–Q3, 3.2–6.3 mV]). Bipolar voltages in denervated areas and 123 I- m IBG transition zones were <0.5 mV, 0.5 to 1.5 mV, and >1.5 mV in 35%, 36%, and 29%, as well as 35%, 35%, and 30%, respectively ( P >0.05). Successful ablation sites were within bipolar voltage–defined scar (7%), border zone (57%), and areas of normal voltage (36%), but all ablation sites were abnormally innervated (denervation/ 123 I- m IBG transition zone in 50% each). Conclusions—: 123 I- m IBG innervation defects are larger than bipolar voltage–defined scar and cannot be detected with standard voltage criteria. Thirty-six percent of successful VT ablation sites demonstrated normal voltages (>1.5 mV), but all ablation sites were within the areas of abnormal innervation. 123 I- m IBG innervation maps may provide critical information about triggers/substrate modifiers and could improve understanding of VT substrate and facilitate VT ablation. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique Identifier: NCT01250912.